2006
DOI: 10.1016/s1472-6483(10)61192-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endometrioma cystectomy on IVF outcome: a prospective randomized study

Abstract: The study was conducted to investigate the effect of conservative surgery of ovarian endometriomas before an ICSI cycle. Ninety-nine patients with endometriomas who were referred to an intracytoplasmic sperm injection (ICSI) cycle were enrolled in the study. The patients were prospectively randomized into two groups; group I (49 patients) underwent conservative ovarian surgery before the ICSI cycle and group II (50 patients) underwent the ICSI cycle directly. The stimulation was started 3 months after the oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(105 citation statements)
references
References 35 publications
4
94
1
6
Order By: Relevance
“…Evidence from a randomized controlled study of patients with endometrioma who either underwent intra-cytoplasmic sperm injection directly or after excision of the endometrioma showed a worse response to ovarian stimulation in the treated ovaries. However, no differences in pregnancy rates were detected (Demirol et al, 2006). Furthermore, there have been two systematic reviews and meta-analyses assessing the impact of surgery for endometriomas on ART outcomes.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…Evidence from a randomized controlled study of patients with endometrioma who either underwent intra-cytoplasmic sperm injection directly or after excision of the endometrioma showed a worse response to ovarian stimulation in the treated ovaries. However, no differences in pregnancy rates were detected (Demirol et al, 2006). Furthermore, there have been two systematic reviews and meta-analyses assessing the impact of surgery for endometriomas on ART outcomes.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…More recently, a study of 99 infertile couples randomized women to surgical excision of endometriomas prior to IVF-ICSI or immediate IVF-ICSI with the endometrioma aspirated at the time of oocyte collection. The study found that the pregnancy rate was similar between the groups [23].These results argue against excision of an endometrioma in women scheduled for IVF as surgery does not appear to improve the chance of pregnancy. Nevertheless, all endometriomas are not the same, and it appears that cysts over 3 cm have a more severe impact on ovarian performance during COH [24].…”
Section: In Vitro Fertilizationmentioning
confidence: 81%
“…Ancak randomize kontrollü çalışmalar YÜT öncesi cerrahinin, başarı şansını arttırmadığını göstermiştir. [19][20][21] Ayrıca cerrahi yapılan kadınlarda, cerrahi yapıl-mayanlara göre stimülasyon daha uzun sürmekte, daha fazla gonadotropin gerektirmekte ve de toplanan oosit sayısı daha az olmaktadır. 20 Bu yüzden bu kadınlarda cerrahi, sadece overlere ulaşılamadı-ğında ya da ağrı tedavisi için düşünülmelidir.…”
Section: Yardimci üReme Tekni̇kleri̇ (Yüt)unclassified